2004
DOI: 10.1007/s00402-004-0763-5
|View full text |Cite
|
Sign up to set email alerts
|

Iatrogenic paraplegia in spinal surgery

Abstract: Operative treatment of scoliosis with a high degree of correction carries a risk of neurological complications of about 0.5%. Mechanical as well as ischaemic damage to the spinal cord can be detected early by means of consistent intraoperative neuromonitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 21 publications
1
28
0
Order By: Relevance
“…The PSF-H group (n = 27 patients) consisted of 23 female and 4 male patients, with a mean age at surgery of 14.9 years (11)(12)(13)(14)(15)(16)(17)(18)(19)(20), and a mean Risser's sign of 2.34 (0-5). The curve patterns according to the Lenke's classification were 11 (40%) type 1, 9 (33.3%) type 2, 3 (11%) type 3, and 4 (15%) type 4.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PSF-H group (n = 27 patients) consisted of 23 female and 4 male patients, with a mean age at surgery of 14.9 years (11)(12)(13)(14)(15)(16)(17)(18)(19)(20), and a mean Risser's sign of 2.34 (0-5). The curve patterns according to the Lenke's classification were 11 (40%) type 1, 9 (33.3%) type 2, 3 (11%) type 3, and 4 (15%) type 4.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the risks of a too aggressive posterior-only correction not preceded by an anterior release should not be underestimated. Overdistraction should be avoided due to the risk of spinal cord ischemia [17]. In the past, it was reported that an intraoperative correction exceeding the preoperative bending correction was one of the factors related to an increased risk of spinal cord injury [58].…”
Section: Discussionmentioning
confidence: 99%
“…Another long series compiled by Delank et al 28 includes an incidence of iatrogenia in scoliosis surgery of 0.55%. In our study, the incidence of SCI following scoliosis was one case, but we could not find the incidence as the patient was referred from another hospital and we do not know the total number of scoliosis interventions that were carried out.…”
Section: Discussionmentioning
confidence: 99%
“…However, the limitation of such procedure is well known and particularly such a test provides information regarding the motor function only. Nevertheless the recent study in major German spine centres [2] document that 63% of patients undergoing surgery for correction of scoliosis are still using the Stagnara Wake-up test as a means of monitoring of the surgical procedure. The electrophysiological monitoring by means of SEP was performed in 18% and the motor evoked potentials by transcranial cortex stimulation were done in Germany only in 9% of the cases (study published in 2005).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study in Germany [2] reviewed retrospectively 1,194 patients in one spine centre being operated over the period of 10 years with spinal fusion and observed that seven patients (0.59%) experienced post surgical complete or incomplete paraplegia. The same group performed an additional survey within 17 German University Clinics and designated centres for spinal surgery and surveyed 3,115 scoliosis surgeries with a frequency of iatrogenic paraplegia of 0.55%.…”
Section: Introductionmentioning
confidence: 99%